2012
DOI: 10.1128/jvi.01550-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Salmonella Bacteriophage SS3e

Abstract: A Salmonella lytic bacteriophage, SS3e, was isolated, and its genome was sequenced completely. This phage is able to lyse not only various Salmonella serovars but also Escherichia coli, Shigella sonnei, Enterobacter cloacae, and Serratia marcescens, indicating a broad host specificity. Genomic sequence analysis of SS3e revealed a linear double-stranded DNA sequence of 40,793 bp harboring 58 open reading frames, which is highly similar to Salmonella phages SETP13 and MB78.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…4A ), including the Salmonella phage SS3e, which shows extremely broad host spectrum against strains of various Salmonella serovars, E . coli , Shigella sonnei , Enterobacter cloacae , and Serratia marcescens 14 and the gene might be obtained from the Salmonella phage genome by horizontal gene transfer during their co-infection of the Salmonella strain or E . coli strain.…”
Section: Resultsmentioning
confidence: 99%
“…4A ), including the Salmonella phage SS3e, which shows extremely broad host spectrum against strains of various Salmonella serovars, E . coli , Shigella sonnei , Enterobacter cloacae , and Serratia marcescens 14 and the gene might be obtained from the Salmonella phage genome by horizontal gene transfer during their co-infection of the Salmonella strain or E . coli strain.…”
Section: Resultsmentioning
confidence: 99%
“…Following the structural components, there is a region encoding small and uncharacterized proteins, which spans about 24 kb. No genes similar to the genes for lysin or holin have yet been detected in the phiAxp-2 genome, which are responsible for host cell disruption during the burst steps of phages 15 , although the clearing of the bacterial culture at a specific time point strongly suggest that they exist.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have characterized a Siphoviridae phage that infects the important nosocomial pathogen A. xylosoxidans . Genomic data are an important resource with which to study and engineer phages to control specific bacterial species 15 , and advances in phage genomic characterization have made phage therapy more feasible in terms of both its logistics and safety 10 . A combination of genomic sequencing and a morphological analysis showed that phiAxp-2 is a member of the family Siphoviridae , and is related to the previously sequenced phage AH2.…”
Section: Resultsmentioning
confidence: 99%
“…This article presents the sequence analysis and a detailed genome annotation of phage phiAxp-1. The genomic data constitute an important resource to study and engineer phages to control specific bacterial species 22 . The analysis showed that phiAxp-1 does not easily fit into previously established groups of dsDNA bacterial viruses and may represent a distinct branch of the Siphoviridae family.…”
Section: Discussionmentioning
confidence: 99%